The Influence of Interdependence in Networked Publics Spheres: How Community-Level Interactions Affect the Evolution of Topics in Online Discourse. Issue 3 (13th May 2021) - Yang, Aimei; Choi, Ian Myoungsu; Abeliuk, Andrés; Saffer, Adam
Abstract: : Investigations of networked public spheres often examine the structures of online platforms by studying users' interactions. These works suggest that users' interactions can lead to cyberbalkanization when interlocutors form homophilous communities that typically have few connections to others with opposing ideologies. Yet, rather than assuming communities are isolated, this study examines community-level interactions to reveal how communities in online discourses are more interdependent than previously theorized. Specifically, we examine how such interactions influence the evolution of topics overtime in source and target communities. Our analysis found that (a) the size of a source community (the community that initiates interactions) and a target community (the community that receives interactions), (b) the stability of the source community, and (c) the volume of mentions from a source community to a target community predicts the level of influence one community has on another's discussion topics. We argue this has significant theoretical and practical implications. Lay Summary: Political discussions online, especially those in the United States, seem to range between harmonious discussions of likeminded people and heated debates that end with few, if any, who have changed their minds. Researchers have often examined these balkanized/polarized situations by studying online communities as isolated echo chambers of opinion. Our study focuses on the interactions between online communities who have different worldviews. We examine communities engaged in the global refugee crisis. We consider how the inter-community interactions influence the agenda of the respective communities. Our longitudinal analysis on the one hand confirms previous studies, namely that intra-community interactions indeed resemble echo chambers. On the other hand, we also find that there is interdependence in the inter-community discussion topics, albeit some communities had greater influence on other communities' discussion topics. For example, larger, more stable communities command more influence.